2014
DOI: 10.1161/circimaging.113.000897
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Very-Low-Dose Radiation Exposure in Cardiac Computed Tomography, Single-Photon Emission Computed Tomography, and Positron Emission Tomography

Abstract: The x-ray tube current, expressed in units of milliamperes (mA), is the number of electrons accelerated across an x-ray (Circ Cardiovasc Imaging. 2014;7:723-734.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Finally, there is a current trend towards lower activities and patient-specific dose protocols. 31 , 32 Lowering the activity can easily be achieved by enlarging the scan time, as both are interchangeable within a certain range. In this study, we showed that a scan time up to 8 minutes does not introduce significant motion.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is a current trend towards lower activities and patient-specific dose protocols. 31 , 32 Lowering the activity can easily be achieved by enlarging the scan time, as both are interchangeable within a certain range. In this study, we showed that a scan time up to 8 minutes does not introduce significant motion.…”
Section: Discussionmentioning
confidence: 99%
“…Positron emission tomography (PET) stress testing, which was not used in PROMISE, may provide lower dose examinations, with expert PET sites reporting low radiation doses on the order of 3 mSv for 82 Rb, 13 N-ammonia, and 15 O-water based protocols. 40 Stress perfusion cardiovascular magnetic resonance (CMR) was not performed in PROMISE, but could have provided an alternative with no radiation dose. 41 …”
Section: Discussionmentioning
confidence: 99%
“…However, high tube currents and low pitch factor both result in high radiation exposure to the patients. To reduce radiation dose from coronary CTA, the prospectively gated transverse acquisition should be considered for patients with stable and low heart rates [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%